Analysis of the Islamic Context In the Independent Learning Curriculum in Biology Lessons - Hartono, Adi; Rahma, Nur Izzaty; Gunawan, Resta; Tampubolon, Sarah Witri; Saputri, Soraya (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This research aims to examine the challenges of implementing an independent curriculum in biology learning. The independent curriculum began to be implemented to facilitate learning in schools based on the principle of independent learning, where teachers and students have the freedom to plan their learning. This type of research is a literature study with a qualitative approach. The data source is secondary because it is obtained from journal articles, scientific publications and other sources related to independent curriculum studies. The data analysis technique is carried out descriptively by analyzing the content of relevant reading sources and can provide an understanding of the findings. Based on studies from several studies, it can be concluded that the implementation of the independent curriculum has a positive impact on improving students' learning abilities. Teachers and students can design the learning process according to learning and teaching styles so that learning is more enjoyable. And there are several Islamic values, namely: The value of mercy (Q.S. Al Anbiya': 107)., the value of trust, (Q.S Al Ahzab: 72), the value of da'wah (Q.S. Fussilat: 33)., the value of tabsyir (Q.S. Al Baqarah: 119), the value of worship (Q.S. Adz Dzariyat: 56 ; Ali Imran: 190-191).